2015
DOI: 10.1186/s13014-015-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone density as a marker for local response to radiotherapy of spinal bone metastases in women with breast cancer: a retrospective analysis

Abstract: BackgroundWe designed this study to quantify the effects of radiotherapy (RT) on bone density as a local response in spinal bone metastases of women with breast cancer and, secondly, to establish bone density as an accurate and reproducible marker for assessment of local response to RT in spinal bone metastases.MethodsWe retrospectively assessed 135 osteolytic spinal metastases in 115 women with metastatic breast cancer treated at our department between January 2000 and January 2012. Primary endpoint was to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 27 publications
5
39
1
Order By: Relevance
“…This may indicate that the effect in ROI-PF was mainly due to BMD changes in the lesions (ROI-ML) and suggests that the irradiated femoral bone inside the radiation field but outside the lesion is unaffected or less affected by RT. A few studies found a smaller BMD increase in irradiated normal-appearing bone surrounding lytic metastases in vertebrae compared with the regions with vertebral lesions 10, 11. However, to our knowledge, the effect of RT on total bone volume in the radiation field has not been studied previously.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This may indicate that the effect in ROI-PF was mainly due to BMD changes in the lesions (ROI-ML) and suggests that the irradiated femoral bone inside the radiation field but outside the lesion is unaffected or less affected by RT. A few studies found a smaller BMD increase in irradiated normal-appearing bone surrounding lytic metastases in vertebrae compared with the regions with vertebral lesions 10, 11. However, to our knowledge, the effect of RT on total bone volume in the radiation field has not been studied previously.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, some studies report a beneficial effect of RT on bone mineral density (BMD),8, 9, 10, 11, 12 which is also the clinical experience of medical specialists. In contrast, this beneficial effect was not confirmed in a recent systematic review 13 .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bone metastases are a growing problem among patients who are living longer, with the spine being the most commonly affected site [2, 3]. Although external beam radiotherapy (EBRT) has long been the main form of treatment for spinal metastases [47], local recurrence in previously irradiated spinal segments has been reported in more than one-third of long-term survivors with malignancy [8]. Since EBRT was failure for the first time, reirradiation of spinal metastases presents a particular therapeutic challenge in radiation oncology.…”
Section: Introductionmentioning
confidence: 99%